Evaluation of California‐Grown Blood and Cara Cara Oranges Through Consumer Testing, Descriptive Analysis, and Targeted Chemical Profiling. Issue 11 (14th October 2019) - Simons, Tyler J.; McNeil, Christopher J.; Pham, Vi D.; Suh, Joon Hyuk; Wang, Yu; Slupsky, Carolyn M.; Guinard, Jean‐Xavier
Abstract : Abstract: The acceptability of Moro, Tarocco, Cara Cara, Shahani, Bream Tarocco, Boukhobza, and Sanguinelli oranges from both commercial and research orchards was tested with adult ( n = 152) and child ( n = 72) consumers. Qualitative focus groups were also conducted to understand consumer familiarity and thoughts about the fruit. Sensory descriptive and chemical analyses were carried out to identify drivers of liking. Overall, consumers preferred the lighter colored varieties consisting of Tarocco, Cara Cara, and Boukhobza. One cluster of adults ( n = 80) showed preferences towards sweet and fruity flavors and away from sourness and citric acid. The second adult cluster ( n = 72) was tolerant of the sour fruit but did not like fruit high in bitterness and flavonoid content. The largest child cluster ( n = 42) showed preferences for samples higher in orange and tropical flavors (Cara Cara, Tarocco, and Boukhobza varieties). The appearance of the Cara Cara was strongly liked by the consumer population in both quantitative and qualitative settings. Hunter scale a color values strongly correlated to the higher berry/dried fruit flavors, and concentrations of naringenin. Focus group participants noted that they were relatively unfamiliar with blood oranges. Growers and producers may want to invest in the lighter colored varieties, such as Cara Cara, Tarocco, Boukhobza and Shahani, as these were liked by a majority of consumers and were low in less desirable sensory characteristics, such as bitterness and sourness. Practical Application: Through consumer tests, sensory evaluation, and chemical analyses, this research uncovered which sensory properties may drive consumer acceptance of blood and Cara Cara oranges, and informed potential production and marketing strategies for increasing their consumption. This information should benefit the citrus industry as a whole and may enhance the use of specialty oranges by the food, beverage, and food service industries.